Mruiʹ toʻ sanʻʹ rhaṅʻʺ reʺ vuiṅʻʺ vanʻʺ kū ññī choṅʻ rvakʻ peʺ (Ranʻ kunʻ Mruiʹ toʻ Caññʻ paṅʻ Sā yā reʺ Koʻmatī, 1992)
Caricatures and cartoons depicting the citizen participation to clean and keep clean the city of Rangoon, Burma.